6. 6•2-1 = 12-1 = 11
9+2 = 11 11 = 1
7. 9•[8-2-3-(9-8)] 9-8 = 1
8-2-3 = 3 • 9 = 27+1 = 28
8. [7•3-(6+9)]/2= 6+9= 15
7•3 = 21 /2 = 10.5
9. 2•10/5+(7+5)/2= 7+5=12
2•10 = 20/2 = 10+12 = 22
10. 2•6-9-[5-(9-7)] 9-7 = 2
5-2 = 3
2•6= 12-9+3 = 3+3=6
11. 10+10/5-8 = 10/5 = 2
10-8+2= 2+2=4
12. [2-(10-8)]•6+3•5 = 10-8=2
2-2= 0 • 6 = 0+3•5 =15
13. 8/2/(6-4) = 6-4 = 2
8/2/2 = 4/2=2
14. 6[5+(14-8)/3] = 14-8=6 = 5+6/3= 2+5= 7•6 = 42
make sure you always use PEMDAS! those brackets are important too. once you do the problem inside the parentheses you go straight to the problem inside the bracket then move further on. please make brainliest :)!!
The ratio 8:1 ,then when it is 1200 is divided by 40=30.30. that admission is 30
3220 / 3 = 1,073.3 recurring <span />
Answer:
1 3/12
Step-by-step explanation:
Oh wait i could read #5 so you make them all have 12 as the denominator then do 78 4/12 - 77 1/12 and you get 1 1/4 or 1 3/12 so then you do 1 3/12 MINUS 77 1/12 and you should get 75 10/12 which is CORRECCTTTTT
THESE ARE THE THREE IN THE TEXT ORDER IN CASE U NEED TO SEE
78 4/12
77 1/12
75 10/12
EVERYTHING IS CORRECTTTTTTTTTTTTTTTTTTTTTT
Answer:
C
Step-by-step explanation:
okay, this is actually pretty easy because it just works with simple translations.
(x+a)^2 + b
if a is positive, the graph shifts left
if a is negative, the graph shifts right
if b is positive, the graph shifts up
if b is negative, the graph shifts down
so since the quadratic, is starts at the origin and is shift 3 to the left, and 2 up:
the equation is
(x+3)^2 + 2